Tecnologia e informação turística para divulgação e preservação do patrimônio cultural em Santa Maria, RS - Stein, Taís Drehmer (2018)
Known as Cultural City, Santa Maria, Rio Grande do Sul, it suffers from the lack of investment in the area of tourism and public policies to promote tourism. This work aims to present the development of an app, an attractive and modern tool to valorize the cultural heritage of the city through tourism. The research problem is focused on how to design an attractive instrument that would contribute to cultural tourism in Santa Maria, providing information and valorizing the city's cultural heritage for the use of different audiences. The main objective is to develop marketing strategies through an app for dissemination and valorize of the tourist attractions of Santa Maria. The specific objectives are: to propose a tour itinerary that contemplates the buildings and monuments that are the Santa Maria historical-cultural heritage, based on already existing promotional materials; to develop a smartphone application that allows route navigation and access to its information; to incorporate services and events related to the visit of tourists and local citizens that coincide with the tour itinerary; to disseminate the app through mobile marketing strategies. The study was developed as an action research, descriptive, with qualitative data analysis. For the creation of the app, an online platform was used, on the Fábrica de Aplicativos website, which was fed with information obtained through surveys of the most relevant tourist attractions in the city of Santa Maria. In relation to the project impacts, the following are highlighted: dissemination and recognition of these attractions; use of innovation as a tool for development and a means of attracting different types of public, knowledge generation about the city’s history, stimulation of the use of technologies and assistance in preserving the county memory and cultural interest. The app obtained an expressive number of downloads and continues to be improved and updated. Due to good results, it is intended to continue the project, increasing the functions of the app, and expanding it to other cities.